Natural biopolymers as proton conductors in bioelectronics. Issue 7 (22nd May 2021) - Jia, Manping; Kim, Jinhwan; Nguyen, Tiffany; Duong, Thi; Rolandi, Marco
Abstract: Bioelectronic devices sense or deliver information at the interface between living systems and electronics by converting biological signals into electronic signals and vice‐versa. Biological signals are typically carried by ions and small molecules. As such, ion conducting materials are ideal candidates in bioelectronics for an optimal interface. Among these materials, ion conducting polymers that are able to uptake water are particularly interesting because, in addition to ionic conductivity, their mechanical properties can closely match the ones of living tissue. In this review, we focus on a specific subset of ion‐conducting polymers: proton (H + ) conductors that are naturally derived. We first provide a brief introduction of the proton conduction mechanism, and then outline the chemical structure and properties of representative proton‐conducting natural biopolymers: polysaccharides (chitosan and glycosaminoglycans), peptides and proteins, and melanin. We then highlight examples of using these biopolymers in bioelectronic devices. We conclude with current challenges and future prospects for broader use of natural biopolymers as proton conductors in bioelectronics and potential translational applications. Abstract :